INTEGRATION OF FINANCIAL AND OPERATIONAL MANAGEMENT IN THE ORGANISATION OF HAJJ AND UMRAH - Loso Judijanto; Oskar Hutagaluh (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
The integration of financial and operational management in the organisation of Hajj and Umrah can be defined as a holistic approach that combines the integrated management of financial and operational aspects in the planning, implementation, and evaluation of Hajj and Umrah services. The concept involves synchronising processes, systems, and resources between finance and operations departments to achieve higher efficiency, improve transparency, and optimise the quality of services to pilgrims. This integration includes aligning budgets with operational activities, utilising information technology to facilitate real-time data and information flow, and faster and more accurate decision- making based on comprehensive analysis of financial and operational aspects. The study in this research uses the literature research method. The results show that the integration of financial and operational management brings significant improvements in efficiency, transparency, and service quality. Key benefits include resource optimisation, increased accountability, faster and more accurate decision-making, and improved pilgrim satisfaction. Challenges in implementing this integration were also identified, including the need for technology investment and organisational culture change. The study's conclusions confirm the importance of financial and operational management integration as a key strategy in dealing with the complexities and modern demands of organising Hajj and Umrah.